Diverticulitis: A Literature Review - Husnul Khotimah, Andi; Firdaus, Nadine Aisyah Sultan; Haikal, Muhammad; Wulandari, Baiq Nurhandini; Zubaedi, Alisha Chaerani; Hanifah, Hanum Retno; Prawira, I Nyoman Dio Yudha; Nurhidayati, Nurhidayati (Jurnal Biologi Tropis, 2025)
Diverticulitis is an inflammatory disease of the intestinal wall that often occurs in the elderly and is commonly located in the sigmoid colon. Risk factors for diverticulitis include a low-fiber diet, obesity and smoking, while physical activity and a healthy diet can lower the risk. Treatment of diverticulitis includes the use of selective antibiotics, especially in patients with complications or high risk, and surgical intervention may be required in complicated cases. The prognosis of the disease depends on age, severity, and the presence of complications, with a significant risk of recurrence in some patients. This paper aims to provide a comprehensive explanation of the definition, classification, epidemiology, etiology, risk factors, pathophysiology, clinical manifestations, management, complications, prognosis, and prevention of diverticulitis. This literature review was conducted using a literature study method, with data sources obtained from online databases such as PubMed, ScienceDirect, ProQuest, and Google Scholar.